Computer Networks as Social Networks: Collaborative Work, Telework, and Virtual Community - Wellman, Barry; Salaff, Janet; Dimitrova, Dimitrina; Garton, Laura; Gulia, Milena; Haythornthwaite, Caroline (Annual review of sociology, 1996)
When computer networks link people as well as machines, they become social networks. Such computer-supported social networks (CSSNs) are becoming important bases of virtual communities, computer-supported cooperative work, and telework. Computer-mediated communication such as electronic mail and computerized conferencing is usually text-based and asynchronous. It has limited social presence, and on-line communications are often more uninhibited, creative, and blunt than in-person communication. Nevertheless, CSSNs sustain strong, intermediate, and weak ties that provide information and social support in both specialized and broadly based relationships. CSSNs foster virtual communities that are usually partial and narrowly focused, although some do become encompassing and broadly based. CSSNs accomplish a wide variety of cooperative work, connecting workers within and between organizations who are often physically dispersed. CSSNs also link teleworkers from their homes or remote work centers to main organizational offices. Although many relationships function off-line as well as on-line, CSSNs have developed their own norms and structures. The nature of the medium both constrains and facilitates social control. CSSNs have strong societal implications, fostering situations that combine global connectivity, the fragmentation of solidarities, the de-emphasis of local organizations (in the neighborhood and workplace), and the increased importance of home bases.